FSTL5 is a marker of poor prognosis in non-WNT/non-SHH medulloblastoma - Remke, Marc; Hielscher, Thomas; Korshunov, Andrey; Northcott, Paul A.; Bender, Sebastian; Kool, Marcel; Westermann, Frank; Benner, Axel; Şeker-Cin, Huriye; Ryzhova, Marina; Sturm, Dominik; Witt, Hendrik; et al. (Journal of clinical oncology, 2011)
Purpose - - Integrated genomics approaches have revealed at least four distinct biologic variants of medulloblastoma: WNT (wingless), SHH (sonic hedgehog), group C, and group D. Because of the remarkable clinical heterogeneity of group D tumors and the dismal prognosis of group C patients, it is vital to identify molecular biomarkers that will allow early and effective treatment stratification in these non-WNT/non-SHH tumors. - - Patients and Methods - - We combined transcriptome and DNA copy-number analyses for 64 primary medulloblastomas. Bioinformatic tools were used to discover marker genes of molecular variants. Differentially expressed transcripts were evaluated for prognostic value in the screening cohort. The prognostic power of follistatin-like 5 (FSTL5) immunopositivity was tested for 235 nonoverlapping medulloblastoma samples on two independent tissue microarrays. - - Results - - Comprehensive analyses of transcriptomic and genetic alterations delineate four distinct variants of medulloblastoma. Stable subgroup separation was achieved by using the 300 transcripts that varied the most. Distinct expression patterns of FSTL5 in each molecular subgroup were confirmed by quantitative real-time polymerase chain reaction. Immunopositivity of FSTL5 identified a large cohort of patients (84 of 235 patients; 36%) at high risk for relapse and death. Importantly, more than 50% of non-WNT/non-SHH tumors displayed FSTL5 negativity, delineating a large patient cohort with a good prognosis who would otherwise be considered intermediate or high-risk on the basis of current molecular subgrouping. - - Conclusion - - FSTL5 expression denoted a dismal prognosis both within and across medulloblastoma subgroups. The addition of FSTL5 immunohistochemistry to existing molecular stratification schemes constitutes a reliable and cost-effective tool for prognostication in future clinical trials of medulloblastoma.
Gesehen am 15.09.2022